An Open-Label, Multicenter, Observational Study of The Effectiveness of The Cefepime/Sulbactam Antibiotic (Maxictam®-AF) In Patients With Intra Abdominal Infection, Nosocomial Pneumonia or Ventilator-Associated Pneumonia (Study MAXI-2019) - S. V. Yakovlev; M. P. Suvorova; A. O. Bykov; S. V. Zhuravel; K. A. Popugaev; L. Yu. Kulagina; I. N. Ochakovskaya; M. G. Fedorova; O. V. Pribytkova; A. A. Zateyshchikova; O. G. Malkova; T. N. Malorodova; et al. (Антибиотики и Химиотерапия)
The aim of the study was to evaluate the effectiveness of cefepime/sulbactam in patients with intra-abdominal infection, nosocomial pneumonia (NP) or ventilator-associated pneumonia (VAP) in actual clinical practice. Material and methods. The study was conducted in 14 Russian Clinics from October 2019 to March 2020. Study design: an open-label, prospective, non-comparative, multicenter, observational study. The study included patients who met the inclusion/exclusion criteria and signed a written informed consent. The studied antibiotic: cefepime/sulbactam (Maxictam®-AF). The primary parameter for effectiveness evaluation was the clinical effect after the conclusion of cefepime/sulbactam therapy — recovery/improvement or no effect. Results. The study included 140 patients (average age — 60.8 years) who received at least one dose of cefepime/sulbactam; 37 of them had intraabdominal infection, 72 — NP, and 31 — VAP. Most of the included patients were in the ICU department (82.1%) and their condition was severe: the average APACHE II score was 15.5 points, SOFA — 5.4 points, the Mannheim peritonitis index value in patients with intra-abdominal infection was from 14 to 35 points, with an average of 24.3 points. The majority of patients treated with cefepime/sulbactam (68.6%) had one or more risk factors for multi-resistant pathogens upon hospital or ICU admission. Cefepime/sulbactam was prescribed as the 1st or 2nd line of empirical therapy at a daily dose of 4 g (in 68.3%), 6 g (2.9%) or 8 g (28.8%); most patients were prescribed cefepime/sulbactam in monotherapy (72.3%). The average duration of therapy with cefepime/sulbactam was 9.6±3.5 days. The final assessment of treatment effectiveness was carried out in 132 patients: recovery or improvement was noted in 80.6% of patients with intra-abdominal infection, the effectiveness in NP and VAP was slightly higher — 95.6 and 89.3%. The effect was absent in 5.3% of patients, relapse or superinfection was noted in 3.0 and 1.5%. The majority of patients (81.3%) treated with cefepime/sulbactam were discharged from the hospital. No serious side effects were observed. In patients with a positive effect, age and values of APACHE II were significantly lower (59.58 years and 14.79 points) compared to those with no effect (67.95 years and 18.39 points). A multivariate analysis found that the probability of recovery of patients treated with cefepime/sulbactam did not depend on the diagnosis of infection, ICU admission, the presence of sepsis or septic shock. Conclusion. The multicenter study has established a high clinical efficacy of cefepime/sulbactam in real clinical practice in the treatment of patients with severe intraabdominal infection, nosocomial pneumonia or ventilator-associated pneumonia.